Analysis of Infiltration in Various Land Use in The Alo River Sub-Region - Wiranto Djauhari; Arthur Gani Koto; Risman Jaya; Tisen Tisen; Sri Rahayu Ayuba; Ahmad Syamsu Rijal (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2023)
In the Alo sub-watershed, the study compares the rates of various types of land use. The Alo sub-watershed is 7,959.98 areas in total. Measurement of infiltration rates for various land uses in the Alo sub-watershed and analysis of differences in infiltration rates for various land uses in the Alo sub-watershed are the problems at hand in this study. The Horton method was used in this study's infiltration measurements. This approach uses a model of time-dependent empirical equations. It is known that multiple infiltration categories exist for plantations, villages, vacant land, bushes, and woods in the infiltration rate class for the kind and usage of dry land used in this study's Alo sub-watershed. It has classes for Fast, Moderate, and Moderate infiltration rates. For the type of land use and paddy field, the infiltration rate falls into the category of being fairly slow. This is due to the high water content of paddy fields, which makes the infiltration process take a while to complete. As a result, the infiltration rate in the Alo sub-watershed, Tibawa District, Gorontalo Regency, and Gorontalo Province reveals that the medium class dominates in the Alo sub-watershed. The cumulative infiltration rate or total amount of infiltrated water is 123,899 mm/hour at point 14 types of vacant land, and 8,476 mm/hour at point 16, which is the smallest cumulative value. The infiltration rate class in the Alo sub-watershed, Tibawa District, Gorontalo Regency, and Gorontalo Province reveals that the Medium Class dominates the sub-watershed.